Acute compartment syndrome in pediatric patients: a case series. Issue 2 (March 2022) - Lin, James; Samora, Walter P.; Samora, Julie B.
Abstract : Pediatric acute compartment syndrome (ACS) is an orthopedic emergency which requires timely recognition and management. There are unique considerations in children, as they may present with a wide array of symptoms and capacities to communicate. We sought to investigate the presentations, treatments and outcomes of pediatric ACS, hypothesizing that decompressive fasciotomy results in good outcomes, even with delayed treatment (>24 h). We performed a retrospective review of pediatric ACS from 2009 to 2018. Exclusion criteria were age ≥18 years, exertional compartment syndrome, and incomplete data. Twenty-one patients (mean age 11 years) were included. Swelling (100%) and worsening pain (100%) were the most common presenting signs and symptoms followed by paresthesias (75%). Increasing analgesia requirements were documented in six (29%) patients. Compartment pressures were measured in 52% of patients. All patients were managed with decompressive fasciotomies, which were performed at a median time of 20 h from injury. Strength and range of motion deficits (10%) were the most commonly reported complications. There were no infections. All patients who were treated in a delayed fashion (≥24 h) were found to have a good functional recovery, but 38% had minor complications. Overall, patients had good outcomes, achieving full functional recovery with return to preinjury activity level. Pediatric ACS should be approached as a distinct clinical entity from adult ACS, where risks of infection and wound complications from delayed fasciotomy generally outweigh the benefits. We recommend considering decompressive fasciotomy for all cases of pediatric ACS, including those with prolonged time from injury to diagnosis.